PELATIHAN PEMBUATAN SABUN SKALA HOME INDUSTRI SEBAGAI RINTISAN USAHA DI DESA SIDOKARE REJOSO NGANJUK - Fitriari Izzatunnisa Muhaimin; Sari Edi Cahyaningrum; Titik Taufikurohmah; Nurhayati (Universitas Negeri Surabaya, 2022)
Livelihoods the people of Sidokare village, Rejoso sub-district, Nganjuk regency are mostly farmers. In addition to planting rice, they also plant shallots which are their signature product. Most of the women in Sidokare village are housewives who are also farmers and farm labourers. However, during the period between the planting season and harvest season, most of them are unemployed and have no income. This is certainly a burden for the family's economy, in addition to the Covid-19 pandemic that causes the price of harvest to be uncertain while the daily needs must still be met. The purpose of this community service activity is to provide training and assistance in the production of home industry scale soap products while still paying attention to the quality that meets health standards by utilizing herbal ingredients. This activity is expected to equip women in Sidokare Nganjuk Village with skills in making home industry soap products that can be used as business startups to support the family economy. As a result of this activity, the community gains skills to produce various liquid soap products that can be marketed in their neighbourhood.